Recurrent Benign Pneumatosis Intestinalis in a Patient With Mixed Connective Tissue Disease - Sahil KOPPIKAR,; David YU,; Mark ROPELESKI,; David ROBERTSON, (Archives of Rheumatology, 2018)
Connective tissue diseases can be associated with rare gastrointestinal complications such as pneumatosis intestinalis and pneumoperitoneum. In this article, we report a unique case of recurrent pneumatosis intestinalis and spontaneous pneumoperitoneum without evidence of peritonitis in a patient with long-standing mixed connective tissue disease. Computed tomography scan of the abdomen and pelvis revealed pneumatosis of the jejunum and intra-abdominal free air, without evidence of perforation. The patient was managed non-operatively. Prior to discharge, on post-admission day two, imaging revealed resolution of the pneumatosis but persistent large volume pneumoperitoneum. It is important for clinicians to recognize pneumatosis and pneumoperitoneum as a possible benign complication in patients with mixed connective tissue disease and differentiate it from ruptured viscous. The management of benign spontaneous pneumoperitoneum can be supportive, thereby avoiding unnecessary investigations and surgery.